Análise da conta vinculada na contratação de serviços terceirizados sob a ótica da teoria dos custos de transação: um estudo em uma Instituição Federal de Ensino Superior - Minchio, Manuella Aparecida (2021)
The insertion of outsourcing brought to the Public Service the need to manage contracts entered into for the provision of continuous labor services. With this advent, problems arose with workers from outsourced companies who often violated their labor rights. In view of the search for safeguarding these guarantees and also removing this subsidiary responsibility from managing servers, the linked deposit account was created. Their insertion in the routine of administrative inspectors resulted in an increase in activities and controls and, in some places, a need to increase personnel, which also implies an increase in costs, impacting the main point that motivated outsourcing, which is cost savings . In this context, the research was guided by the following objective: to investigate and understand the impact of the linked deposit account in the management of outsourcing contracts within the scope of the Federal Institute of Espírito Santo - Campus Cariacica in the period 2015-2020. In theoretical terms, the Transaction Costs Theory is approached as a way to identify the occurrence or not of costs generated with the CDV. As mentioned by Williamson (1985) any issue that arises from a contracting problem can be examined by the Transaction Cost Theory. As for the methods and procedures, a qualitative approach was adopted through descriptive, explanatory and documentary research. A questionnaire was applied to managers and inspectors of the contract sector at IFES Campus Cariacica; in a complementary way, a documentary research was carried out with the labor processes in the period 2015-2020. In the results achieved, it was possible to identify the advantages and disadvantages of CDV for outsourced workers and Public Administration. There was also a need for a control platform or software to assist in monitoring the CDV, in addition to continuous training aimed at legislation and labor calculations. In view of the results achieved, a diagnostic report of the CDV was prepared as a technical product, which proposed the offer of courses focused on legislation, and labor calculations, in addition to the creation/development of a platform or control software to assist in the maintenance of the CDV.